(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2022)
The author offers an overview of the Afghan people’s situation after the restoration of the Taliban regime. Following an analysis of the measures enacted by the Taliban regime to limit the exercise of some fundamental rights, the A. warns about the negative consequences that would arise as a consequence of the possible recognition by the international community of the legitimacy of the Taliban regime established in Afghanistan in August 2021. Eventually, the A. calls on foreign countries not to ignore the abuses committed by the Taliban and urges the international community’s intervention to support the Afghan population.